Meningkatkan Berpikir Komputasi Siswa Melalui Aktivitas Unplugged: Studi Action Research pada Binary Search Trees - Andy Agustian; Elisa Rosa; Rangga Destian; Lala Septem Riza; Muhammad Nursalman; Rasim Rasim; Rani Megasari; W. Wahyudin (Politeknik Kampar, 2024)
Computational thinking is an essential skill in the digital age that includes problem solving, data analysis, and understanding algorithms. Unplugged activities, which introduce the concept of computing without electronic devices, are an effective and inclusive alternative in education, especially in environments with limited access to technology. This study aims to investigate the improvement of students' computational thinking through unplugged activities focusing on Binary Search Trees (BST). The method used is action research with the Kurt Lewin model, involving 42 6th grade elementary school students. The ISTE instrument was used to measure computational thinking skills. The results showed an increase in computational thinking skills, with 14.29% of students still not developing, 83.33% of students starting to develop, and 2.38% of students developing as expected. In conclusion, unplugged activities focusing on BST can significantly improve students' computational thinking skills, offering an innovative teaching method that can be applied in various educational contexts.